2015
DOI: 10.1016/j.jsps.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin therapy in critically ill patients on continuous renal replacement therapy; are we doing enough?

Abstract: Therapeutic vancomycin levels are difficult to maintain in critically ill patients who are receiving IV vancomycin therapy whilst on CRRT. Aggressive dosing schedules and frequent monitoring are required to ensure adequate vancomycin therapy in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Dose recommendations for vancomycin in CRRT vary widely in the literature from 500 mg every 12 h, to 1000 mg every 48 h, to continuous infusions 9–13 . Researchers have found that vancomycin concentrations are often subtherapeutic in patients on CRRT 14–16 . A study by Franzee et al found that only 37% of patients achieved target trough concentration, defined as 10–15 mcg/ml or 15–20 mg/L, when vancomycin was dosed based on institutional guidelines of 15–20 mg/kg every 24 h. Failure to achieve target trough was more common in patients on high ultrafiltration rates of >30 ml/kg/h 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dose recommendations for vancomycin in CRRT vary widely in the literature from 500 mg every 12 h, to 1000 mg every 48 h, to continuous infusions 9–13 . Researchers have found that vancomycin concentrations are often subtherapeutic in patients on CRRT 14–16 . A study by Franzee et al found that only 37% of patients achieved target trough concentration, defined as 10–15 mcg/ml or 15–20 mg/L, when vancomycin was dosed based on institutional guidelines of 15–20 mg/kg every 24 h. Failure to achieve target trough was more common in patients on high ultrafiltration rates of >30 ml/kg/h 14 .…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] Researchers have found that vancomycin concentrations are often subtherapeutic in patients on CRRT. [14][15][16] A study by Franzee et al found that only 37% of patients achieved target trough concentration, defined as 10-15 mcg/ml or 15-20 mg/L, when vancomycin was dosed based on institutional guidelines of 15-20 mg/ kg every 24 h. Failure to achieve target trough was more common in patients on high ultrafiltration rates of >30 ml/kg/h. 14 Continuous infusion vancomycin is an alternative to intermittent dosing and may achieve AUC24/MIC ratio ≥400 more consistently.…”
Section: Pharmacokinetic Data Provided By Neely Et Al Demonstrated High Inter-mentioning
confidence: 99%
“…Although vancomycin clearance in patients receiving CVVHDF appears to be easily predicted by the known principles of hemofiltration, hemodialysis, and pharmacokinetic properties of vancomycin, it is recommended that TDM be performed instead of relying only on the predicted value because the actual clinically measured value is often different from the predicted value [ 3 , 7 , 8 , 14 , 35 , 36 ]. In particular, vancomycin has a narrow therapeutic range, thus accurate prediction and maintenance of proper serum concentration are more important [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…About 80-90% vancomycin is excreted as unchanged drug in the first 24 h from urine. Vancomycin serum levels are difficult to maintain in CRRT patients (Omrani et al, 2015), and are significantly affected by CRRT intensity (Beumier et al, 2013). Early study suggested vancomycin 1 g q48h under CVVH and 1 g q24h under CVVHD and CVVHDF (Trotman et al, 2005).…”
Section: Vancomycinmentioning
confidence: 99%